1966
DOI: 10.1111/j.1365-2672.1966.tb03491.x
|View full text |Cite
|
Sign up to set email alerts
|

The Microflora of Poorly Cleansed Farm Dairy Equipment

Abstract: A series of 170 rinses and 14 milk residue deposits from poorly clean& dairy equipment on 136 farms, giving colony counts a t 30" of > 106/ft' for rinses or /g wet w t for residues, were claasitied into 8 groups according to the composition and milk spoilage activity of their microflora. Five of the groups were dominated by active milk spoilage types of bacteria and three by inactive organisms. Micrococci, coryneform bacteria and aerobic sporeforming rods dominated the microflora of 1/3 of the 184 samples. Gra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

1967
1967
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 19 publications
1
3
0
Order By: Relevance
“…The associations between LPC, CC, and the majority of equipment hygiene-related factors support previous reports by Thomas et al (1966) and Reinemann et al (2003), who indicated that improperly cleansed dairy equipment and bacterial incubation on milk contact surfaces are the main source of thermoduric and gramnegative rods. These results also support the conclusion by Villar et al (1996) that thermoduric and coliform counts characterize hygienic condition of dairy equipment.…”
supporting
confidence: 88%
“…The associations between LPC, CC, and the majority of equipment hygiene-related factors support previous reports by Thomas et al (1966) and Reinemann et al (2003), who indicated that improperly cleansed dairy equipment and bacterial incubation on milk contact surfaces are the main source of thermoduric and gramnegative rods. These results also support the conclusion by Villar et al (1996) that thermoduric and coliform counts characterize hygienic condition of dairy equipment.…”
supporting
confidence: 88%
“…Thus, it may be that milks with high total counts contain a greater proportion of these organisms so that the level of catalase remains unchanged. Such a change in bacterial flora has been reported (Thomas et al 1963), but is not great enough to fully explain the results.…”
Section: Results and Discussion R A W M I L K Q U A L I T Ymentioning
confidence: 59%
“…When milking equipment CIP procedures are performed using hot water (≥70°C), the microflora recovered from the pipeline surface is mostly composed of thermoduric bacteria such as micrococci, coryneforms, and aerobic spore-forming rods. However, gram-negative rods and streptococci may become the dominant species recovered from the pipeline surface on farms in which cleaning procedures were carried out at lesser temperatures (Jackson and Clegg, 1965;Thomas et al, 1966Thomas et al, , 1971. When cleaning failures occur, residual soil may facilitate bacterial attachment, survival, and Wash failures were defined based on the last wash before a visit as failures to reach the normal wash water temperature (<20% of a farm's preset temperature), failure to dispense a farm's preset amount of detergent during wash, lack of water flow through ≥1 milking unit, or skipped wash.…”
Section: Discussionmentioning
confidence: 99%